An assessment model of monitoring risk in deep excavation based on fuzzy theory. Issue 2 (February 2020) - Long, Lin; Li, Zhida
In order to better evaluate the monitoring risk of deep excavation, an assessment model based on fuzzy theory was established by combining the uncertainty and membership degree of evaluation indexes with the fuzziness of experts' comments. Firstly, considering the risk sources as evaluation indexes, the monitoring risk evaluation system for deep excavation was establish, and the risk evaluation function was constructed. Secondly, the risk assessment model based on fuzzy theory was put forward, analytic hierarchy process was used to determine the weight of evaluation indexes, and expert evaluation weight was introduced to correct the evaluation function. Finally, comprehensive risk grade in deep excavation was obtained and the risk decisions were put forward by calculating the value of modified evaluation function. Through the application of the monitoring risk assessment model in the deep excavation of World Trade Group, the results are in accordance with the engineering practice. The results suggest that the model based on fuzzy theory is efficient for evaluating the monitoring risks and can be used in the application of deep excavation evaluation. Meanwhile, the applicability and accuracy of the assessment model are verified.